2020
DOI: 10.3390/jcm9051389
|View full text |Cite
|
Sign up to set email alerts
|

Urine Proteomic Study in OAB Patients—Preliminary Report

Abstract: Overactive bladder (OAB) is defined by International Urogynecological Association (IUGA)/ International Continence Society (ICS) as urinary urgency, usually accompanied by frequency and nocturia, with or without urgency urinary incontinence, in the absence of urinary tract infection (UTI) or other obvious pathology. The pathophysiology of OAB is not well understood, however a number of different proteins and cytokines including vascular cell adhesion molecule-1 (VCAM-1) were found to be important in regulating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Our findings may indicate a disruption in the capability of the urinary bladder tissue to adequately respond to external stimuli in OAB patients—possibly due to an altered immune response. One smaller proteomic study on OAB identified the protein VCAM-1 as only significantly different protein when compared to controls [ 18 ]. VCAM-1 protein plays a role in immune response and leukocyte emigration and can be located in the pathway categories “extracellular matrix organization” and “immune system”.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings may indicate a disruption in the capability of the urinary bladder tissue to adequately respond to external stimuli in OAB patients—possibly due to an altered immune response. One smaller proteomic study on OAB identified the protein VCAM-1 as only significantly different protein when compared to controls [ 18 ]. VCAM-1 protein plays a role in immune response and leukocyte emigration and can be located in the pathway categories “extracellular matrix organization” and “immune system”.…”
Section: Discussionmentioning
confidence: 99%
“…We have successfully used this approach previously, and were able to identify a urinary proteomic pattern in women with stress urinary incontinence [ 16 , 17 ]. Preliminary findings from a urinary proteomic study on OAB describe vascular cell adhesion protein (VCAM-1) in significantly different abundance in OAB patients compared to controls, but this study included only 16 samples [ 18 ]. Identification and comparison of the urinary proteome in patients with OAB should contribute to a more profound understanding of the etiology and could provide a basis for new treatment options.…”
Section: Introductionmentioning
confidence: 99%
“…Its incidence is assumed to be as high as 52-67 per 100,000 cases in the United States [40]. Although OAB and IC/PBS are considered to be separate pathological conditions there is growing scientific evidence that both are related to structural, synaptic, and complex signaling pathway changes that trigger altered bladder sensation [41]. Recently, the efficacy of intravesical instillation with PRP and hyaluronic acid for cyclophosphamide-induced acute IC/PBS was investigated in a rat model.…”
Section: Urogynecologymentioning
confidence: 99%
“…Recent studies have shown that the vicious cycle of chronic inflammation and related stresses is associated with several diabetic complications, including atherosclerosis, nephropathy, and cystopathy, which have been demonstrated in both human and animal experiments ( 15 17 ). The pathophysiology of OAB is not well understood; however, chronic systemic inflammation and bladder urothelial inflammation, including some inflammatory proteins and cytokines, may contribute to the onset of OAB ( 15 , 18 ). An increasing number of studies suggest that DBD and OAB are slow-onset and slow-progressing complications, and among them, inflammatory factors such as IL-1β and NLRP3 play an important role ( 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%